GAMBARAN KARAKTERISTIK KOMPLIKASI MIKROVASKULER NEUROPATI PERIFER PADA PENDERITA DM TIPE II - Sri Rahayu Lestari; Yesi Hasneli N; Ganis Indriati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Diabetes mellitus (DM) is a chronic disease that occurs when the body cannot produce enough insulin or when the body cannot effectively use insulin. Symptoms of DM are grouped into two types, namely type I DM and type II DM, type I DM is insulin dependent while type II DM is caused by a combination of insulin resistance in the body. DM complications can cause peripheral neuropathy, which is one of the microvascular complications of DM which can cause damage to autonomic, sensory and motor nerve function. This study aims to describe the characteristics of microvascular complications of peripheral neuropathy in DM patients in the Rejosari Public Health Center, Pekanbaru. The research design was descriptive with a cross sectional approach. The sample in this study were 30 respondents using purposive sampling technique. The measuring instrument used was the peripheral neuropathy microvascular observation sheet. The analysis used is descriptive. The results showed that the majority of respondents had moderate peripheral neuropathy damage as many as 26 respondents (86.7%). The majority of respondents experienced multiple autonomic damage as many as 30 respondents (100.0%) on the sensory nerve examination, it was found that the majority of respondents felt no sensation with 17 respondents (56.7%) and the results of motor nerve examination the majority of respondents experienced a decrease in muscle strength by 19 respondents (63.3%). This study suggests that screening and counseling at the health center regarding microvascular neuropathy complications and how to treat complications of peripheral neuropathy in type II DM patients is very important.Keywords: Diabetes mellitus, microvascular complications, neuropathy